TAROGE-M: Radio Observatory on Antarctic High Mountain for Detecting Near-Horizon Ultra-High Energy Air Showers - Wang, Shih Hao; Chen, Pisin; Chen, Yaocheng; Huang, Jian Jung; Huang, Ming Huey Alfred; Kuo, Chung Yun; Leung, Chung Hei; Liu, Tsung Che; Nam, Jiwoo; Shiao, Yu Shao Jerry; Wang, Min Zu; Wang, Shih Hao; et al. (Proceedings of Science, 2022)
The TAROGE-M observatory is an autonomous antenna array on the top of Mt. Melbourne (∼2700 m altitude) in Antarctica, designed to detect radio pulses from ultra-high energy (over 1017 eV) air showers coming from near-horizon directions. The targeted sources include cosmic rays, Earth-skimming tau neutrinos, and most of all, the anomalous near-horizon upward-going events of yet unknown origin discovered by ANITA experiments. The detection concept follows that of ANITA: monitoring large area of ice from high-altitude and taking advantage of strong geomagnetic field and quiet radio background in Antarctica, whereas having significantly greater livetime and scalability. The TAROGE-M station, upgraded from its prototype built in 2019, was deployed in January 2020, and consists of 6 log-periodic dipole antennas pointing horizontally with bandwidth of 180-450 MHz. The station is then calibrated with drone-borne transmitter, with which the event reconstruction obtained ∼0.3° angular resolution. The station was then smoothly operating in the following month, with the live time of ∼ 30 days, before interrupted by a power problem, and its online filtering has identified several candidate cosmic-ray events and sent out via satellite communication. In this paper, the instrumentation of the station for polar and high-altitude environment, its radio-locating performance, the preliminary result on cosmic-ray detection, and the future extension plan are presented.
CRIS-Team Scopus Importer:2023-08-15